2020
DOI: 10.2196/14584
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Housing First and Traditional Homeless Service Users in Eight European Countries: Protocol for a Mixed Methods, Multi-Site Study

Abstract: Background Homeless services expend considerable resources to provide for service users’ most basic needs, such as food and shelter, but their track record for ending homelessness is disappointing. An alternative model, Housing First, reversed the order of services so that homeless individuals are offered immediate access to independent housing, with wraparound supports but no treatment or abstinence requirements. Although the evidence base for Housing First’s effectiveness in ending homelessness i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The leaders of the service users' study, who were based in Ireland, developed a protocol that was followed by participating research teams. The protocol, described elsewhere (Greenwood, Manning, O'Shaughnessy, Cross, et al 2020) included guidance for participant recruitment, consent, interview schedule administration, and analysis. We used this protocol together with biannual meetings, and regular communication with study consortium partners to help standardise study activities across the eight countries and reduce inconsistencies in procedural implementation.…”
Section: Study Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaders of the service users' study, who were based in Ireland, developed a protocol that was followed by participating research teams. The protocol, described elsewhere (Greenwood, Manning, O'Shaughnessy, Cross, et al 2020) included guidance for participant recruitment, consent, interview schedule administration, and analysis. We used this protocol together with biannual meetings, and regular communication with study consortium partners to help standardise study activities across the eight countries and reduce inconsistencies in procedural implementation.…”
Section: Study Contextmentioning
confidence: 99%
“…Research teams in each country identified HF programmes according to study protocol (Greenwood, Manning, O'Shaughnessy, Cross, et al 2020), which stipulated that eligible programmes followed the principles of the Pathways Housing First model (Tsemberis, Gulcur, and Nakae 2004). Participants in SS were recruited from temporary shelter accommodation, women's refuges, drop-in psychiatric services, and night shelters, for example.…”
Section: Programme Selectionmentioning
confidence: 99%
“…As part of larger investigation of experiences of homelessness in Europe [ 81 ], data were collected at two-time points [Time 1 (T1) and Time 2 (T2)] from adults engaged either with a Housing First programme or a service at any step in the staircase of transition (i.e., outreach, emergency services, short-term, or long-term accommodation), hereafter referred to as staircase services (SS). At T1, participants were age 18 or older and sufficiently fluent in the language of their country of residence to understand the questionnaire and consenting materials.…”
Section: Methodsmentioning
confidence: 99%
“…In this larger project, we took a social justice approach to understand the phenomenon of chronic homelessness in Europe from multiple perspectives: service users, service providers, stakeholders, and the public. As part of this larger project, we invited adults engaged in either any step of the staircase of transition or with a Housing First programme to complete a larger questionnaire comprised of a range of measures that assessed aspects of their experiences of homelessness, homeless services, and well-being at two time points [ 81 ]. Here, we used data obtained from participants on the new Measure of Achieved Capabilities in Homeless Services (MACHS) to assess its factor structure, construct validity, and concurrent validity.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers entered participants' responses into a standardized data file that was sent to the second author, who cleaned, merged and managed all 16 (eight countries, two time points) data sets. See (Greenwood et al, 2020a) for more details on recruitment, data collection and data management procedures.…”
Section: Recruitment and Data Collection Proceduresmentioning
confidence: 99%